إرساء نموذج لمؤشرات اتخاذ قرار الاستثمار في البورصة(2005-2009) - دادن, عبد الغفور; بختي, إبراهيم (جامعة الوادي - University of Eloued, 2014)
يعتبر التمويل من بين الاهتمامات البحثية في ميدان المالية فهو بذلك إحد الجوانب التي لا زالت مطروحة للنقاش، فالأسواق المالية إحدى أشكال التمويل التي تلجأ إليها المؤسسات، بهدف نقل التدفقات المالية من الوحدات ذات الفائض إلى الوحدات ذات العجز اعتمادا على الأوراق المالية. إن الاستثمار يحتاج إلى استراتيجيات واضحة يجب إتباعها أثناء اتخاذ القرار حتى لا يتفاجئ المستثمرون بالأزمات وتذبذبات الأسعار صعودا ونزولا ولكن ما هي المؤشرات التي تساعد المستثمر على اتخاذ قرار الاستثمار في البورصة؟ هل يتأثر القرار بمتغيرات من داخل السوق فقط أم أن هناك عوامل أخرى تأثر فيه ويغفل عنها المستثمر؟ ولهذا جاءت هذا الورقة لتحاول بناء نموذج رياضي للمؤشرات بهدف ترشيد قرار الاستثمار في بورصة الأوراق المالية ووقع اختيارنا على الأسهم المسعرة في بورصة الكويت باعتبار هذه الأخيرة إحد نماذج البورصات العربية الأكثر تطورا. Finance is one of the research interests in the field of finance. It is one of the aspects that is still under discussion. Financial markets are one of the forms of financing used by institutions in order to transfer financial flows from surplus units to deficit units based on securities. The investment needs clear strategies to be followed during the decision-making so as not to surprise investors with crises and fluctuations of prices up and down, but what indicators that help the investor to decide to invest in the stock market? Is the decision affected by variables from within the market only or are there other factors affected by and overlooked by the investor? Therefore, this paper came to try to build a mathematical model of the indicators in order to rationalize the decision to invest in the stock exchange and our choice of shares quoted on the Kuwait Stock Exchange as the latter one of the models of the most advanced Arab stock exchanges.
مقال
Keywords: القرار، البورصة، الأوراق المالية، المؤشر; Decision, stock exchange, stock, index